„Autentyczna interpretacja”. (Nie)przestrzeganie prawa autorskiego i konwencji międzynarodowych w stosunku do wydawców i twórców zagranicznych w czasie stalinizmu w świetle materiałów Centralnego Urzędu Wydawnictw, Przemysłu Graficznego i Księgarstwa - Chamera-Nowak, Agnieszka (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
In 1952, the Communists changed the copyright law in Poland that limited copyright protection and linked it to censorship. From the very beginning, however, they deliberately violated copyright laws and international conventions, including the Berne Convention which Poland had been a member of since 1920. The new law strengthened government control over publishing policies and over the transmission of intellectual content that ultimately led to restrictions on the freedom of expression. In particular, the law introduced strict rationing of authors’ earnings, which ceased to be market-driven and depended on administrative decisions. In the case of translations, noncompliance with international regulations led to the withholding of approvals for Polish translations and prevented Polish literature from entering foreign markets, especially Western ones. Books were published without translation approvals, and royalties were charged in violation of international rules. Additionally, payments were withheld especially to Western countries, and the provisions of publishing contracts were not respected. Foreign publishing agencies were abolished and trade contacts were taken over by a state agency. These practices resulted in a significant deterioration of contacts with foreign publishers, including those from the countries in the so-called Eastern Bloc. The result was a narrow readership of foreign literature (especially Western literature), a reduction in the quality of the translations of both Polish and foreign authors, and the absence of translated Polish literature.